Duration of Breastfeeding in Infancy and Levels of Central Adiposity and Systemic Inflammation in Early Middle Adulthood - Thomas W. McDade, PhD; Jessica A. Polos, PhD; Kiarri N. Kershaw, PhD; Taylor W. Hargrove, PhD; Stephanie M. Koning, PhD (AJPM Focus, 2025)
Introduction: Overweight, obesity, and systemic inflammation contribute to chronic degenerative diseases that are major public health burdens associated with aging. This longitudinal cohort study investigates whether the duration of breastfeeding in infancy predicts waist circumference and chronic systemic inflammation in early middle adulthood. Methods: Survey-weighted regression models were implemented with data from the National Longitudinal Study of Adolescent to Adult Health, a nationally representative sample of adults (aged 33–44 years) with information on breastfeeding history as well as measures of waist circumference, C-reactive protein, and interleukin 6. Analyses focused on 3,417 and 3,570 participants with C-reactive protein and interleukin 6 measurements, respectively. Fixed-effects regression models were also used to analyze between-sibling differences in breastfeeding duration, waist circumference, and C-reactive protein/interleukin 6. C-reactive protein and interleukin 6 were quantified in serum with highly sensitive particle-enhanced nephelometric and electrochemiluminescent immunoassays, respectively. Results: Longer duration of breastfeeding was associated with significantly lower waist circumference and lower C-reactive protein. Results were similar for interleukin 6 but statistically weaker. For individuals who were breastfed for 6–12 months and those not at all, marginal mean waist circumference was 94.8 cm (95% CI=92.5, 97.1) and 101.7 cm (95% CI=100.2, 103.2), respectively. Marginal mean C-reactive protein was 1.59 mg/L (95% CI=1.38, 1.84) versus 2.10 mg/L (95% CI=1.97, 2.24). Waist circumference mediated 57.3%–93.8% of the associations between breastfeeding duration and C-reactive protein, depending on duration category. Breastfeeding duration was negatively associated with waist circumference and inflammation in sibling comparisons, but estimates were imprecise and not statistically significant. Conclusions: The convergence of obesogenic environments and low uptake of breastfeeding for cohorts born after the historical nadir of breastfeeding in the U.S. may contribute to epidemics of overweight/obesity and chronic inflammation that presage risk for chronic degenerative diseases of aging.